Evaluating white matter integrity in the auditory cortex in noise-induced hearing loss: A DTI study - Mohd Khairul Izamil, Zolkefley; Rajeev Shamsuddin, Perisamy; Ailin, Razali; Daud, Adam; Muhamad Ariff, Muhamad Noordin (Springer, 2025)
The auditory cortex is essential for processing auditory stimuli, encompassing specialized regions like A1, A4, A5, LBelt, MBelt, and PBelt, each playing distinct roles in auditory information processing. Noise-Induced Hearing Loss (NIHL) poses a significant public health concern which it can severely affect communication abilities, social interaction, and overall quality of life, leading to social isolation, depression, and reduced cognitive functioning. NIHL characterized by cochlear hair cell damage and subsequent auditory pathway impairment. This cross-sectional study investigates the relationship between Fractional Anisotropy (FA) values, indicative of white matter integrity measured via diffusion tensor imaging (DTI), and neural responses to various sound frequencies across specific auditory cortex regions. Thirty-one male subjects, comprising sixteen NIHL patients and fifteen with normal hearing, underwent MRI scans to assess FA values in auditory cortex. Significant correlations were found, particularly in left A4, left MBelt and right PBelt with specific frequencies of sounds (pþinspace<þinspace0.05), indicating associations between FA values and frequency-specific auditory processing. Findings underscore the impact of NIHL on auditory cortex white matter integrity and highlight region-specific vulnerabilities and adaptations to auditory stimuli. These insights could inform targeted interventions to preserve or restore auditory function in individuals affected by NIHL.